2012
DOI: 10.1364/ol.37.002724
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of spatial coherence through diffraction from a transparent mask with a phase discontinuity

Abstract: We describe a robust method by which the spatial coherence from all pairs of points along a line may be simultaneously acquired from an image formed by diffraction from a phase discontinuity. In contrast to other methods, this approach can accurately reveal weak correlations in the tails of a coherence function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…A generalized source as in (11) satisfying Eqs. (12,13) is situated at the plane z = 0. At the detection plane z = d, the coherence G d (y 1 , y 2 ) is well approximated by…”
Section: Propagation Of Fields Produced By a Generalized Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…A generalized source as in (11) satisfying Eqs. (12,13) is situated at the plane z = 0. At the detection plane z = d, the coherence G d (y 1 , y 2 ) is well approximated by…”
Section: Propagation Of Fields Produced By a Generalized Sourcementioning
confidence: 99%
“…The coherence function G relating two points x 1 , x 2 in a quasi-monochromatic scalar field is given by G(x 1 , x 2 ) = U (x 1 )U * (x 2 ) , where • represents an ensemble average, and U (x) is one realization from the ensemble [1]. This coherence function can be obtained by various measurement strategies, e.g., through the use of double slits [2][3][4][5][6], non-redundant arrays of apertures [7,8], lateral-shearing Sagnac and reversed-wavefront Young interferometers [9][10][11], microlens arrays [12], and phase-space methods [13][14][15]. The intensity of the field I is subsumed in the coherence function and lies along its diagonal I(x) = G(x, x).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that one can reduce turbulence-induced scintillation (i.e., intensity fluctuation) through manipulating the correlation functions of partially coherent beams [29,30], which makes partially coherent beams with prescribed correlation functions attractive for free-space optical communications. Various methods have been developed to generate partially coherent beams with prescribed correlation functions and measure their correlation functions [17,28,[30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches make use of non-redundant arrays of apertures to multiplex interferograms [24,25], a pair of non-parallel slits for multiplexing one-dimensional interferograms [26,27], or exploit wavefront sensors [28]. Another strategy for acquiring the spatial coherence function relies on phase-space methods that exploit the connection between spatial coherence and the Wigner distribution associated with the field [29][30][31].…”
Section: Introductionmentioning
confidence: 99%